The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1038/srep11560
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid stem cells provide considerable advantages in epidermal regeneration: B7H4 creates a moderate inflammation microenvironment to promote wound repair

Abstract: The current treatments for severe skin injury all involve skin grafting. However, there is a worldwide shortage of donor skin tissue. In this study, we examined the advantages of using human amniotic fluid stem (hAFS) cells in skin wound healing. In vitro, hAFS cells differentiate into keratinocytes (termed hAFS-K). Like keratinocytes, hAFS-K cells express the markers K5, K14, K10 and involucrin; display typical cellular structure, including a tonofibril-rich cytoplasm; and construct a completely pluristratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…Rodent AFSC closely resemble human AFSC in their growth properties and capacity for in vitro differentiation. Although expression of CD117 declines (and ultimately disappears) with this culture methodology [26], expression of some of the pluripotency (c-Myc, Oct-4, SSEA4) [36,37], endothelial (ETV2, FLI1), and all of the mesenchymal (CD29, CD44, CD73, CD90, CD105) markers is maintained [26]. Growth kinetics analysis of cultured AFSC has shown exponential growth, reaching up to 250 population doublings without any signs of slower proliferation or senescence [17,25,27].…”
Section: Culturementioning
confidence: 97%
“…Rodent AFSC closely resemble human AFSC in their growth properties and capacity for in vitro differentiation. Although expression of CD117 declines (and ultimately disappears) with this culture methodology [26], expression of some of the pluripotency (c-Myc, Oct-4, SSEA4) [36,37], endothelial (ETV2, FLI1), and all of the mesenchymal (CD29, CD44, CD73, CD90, CD105) markers is maintained [26]. Growth kinetics analysis of cultured AFSC has shown exponential growth, reaching up to 250 population doublings without any signs of slower proliferation or senescence [17,25,27].…”
Section: Culturementioning
confidence: 97%
“…In this study, we clearly demonstrated that hAFSCs can cover the MMC defect and that some hAFSCs directly differentiate into cytokeratin-expressing cells, a main component of the skin epidermis. Previously, we and other groups reported that hAFSCs themselves and their secretomes can accelerate wound closure by enhancing reepithelialization using a dorsal excisional cutaneous wound model in BALB/c mice [20,32,33]. Furthermore, hAFSCs promote cutaneous wound closure through the direct differentiation into keratinocytes in vivo and have the potential to differentiate into epidermal-lineage cells including keratinocytes of various maturity levels in vitro [32].…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we and other groups reported that hAFSCs themselves and their secretomes can accelerate wound closure by enhancing reepithelialization using a dorsal excisional cutaneous wound model in BALB/c mice [20,32,33]. Furthermore, hAFSCs promote cutaneous wound closure through the direct differentiation into keratinocytes in vivo and have the potential to differentiate into epidermal-lineage cells including keratinocytes of various maturity levels in vitro [32]. Based on these findings, our data indicated that hAFSCs attach to the surface of the spinal cord and cover the lesion with neoepidermal cells that directly differentiate from hAFSCs and promote epidermal ingrowth stimulated by some hAFSCs-derived paracrine mediators, leading to protection from the "second hit" during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…They are easily accessible and readily available from amniocentesis samples that would otherwise be discarded. Besides the high proliferation capacity and differentiation potential, hAFSCs exhibit a low immunogenicity and immunoregulatory function [4]. Thus, hAFSCs possess considerable advantages that may render them useful for tissue engineering or in the treatment of various autoimmune diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Our and many studies from other groups have confirmed that hAFSCs can be cultured in vitro through adherent growth; they have the features of rapid growth and a fibroblast-like appearance. hAFSCs have been identified to express the phenotypic markers of mesenchymal stromal cells (MSCs) [6][7][8], including CD29, CD44, OCT-4, and CD105; however, they negatively express human leukocyte antigen DR (HLA-DR) and the hematopoietic lineage marker CD34 [4,5,9]. MSCs have potent immunomodulatory properties and target the proliferation and differentiation of a variety of immune cells.…”
Section: Introductionmentioning
confidence: 99%